Meta-analysis of the effect of low-protein diets on the growth performance, nitrogen excretion, and fat deposition in broilers - de Rauglaudre, Théophane; Méda, Bertand; Fontaine, Simon; Lambert, William; Fournel, Sébastien; Létourneau-Montminy, Marie-Pierre (Frontiers in Animal Science, 2023)
In broilers, the impacts of crude protein (CP) reduction on animal performance are heterogeneous. This could limit the use of this strategy in commercial farms despite its potential to improve the sustainability of production. The objective of this meta-analysis was to study the effect of lowering dietary CP in fast-growing broilers with a focus on growth performance. A database was built from 29 papers published after 2016, for a total of 106 trials and 268 treatments. To be included, trials had 2 This is a provisional file, not the final typeset article to be iso-energy and iso-lysine. Trials in which the growth rate for the control treatment was below 90% of the genetic potential of birds were not included. The effect of CP level was analyzed by multiple linear regression with the trial as a random effect. A sub-sample of 33 trials (AACON) met the recommended amino acid (AA): lysine ratios for indispensable AA. In this sub-database, average daily gain and average daily feed intake were maintained when dietary CP was reduced. The feed conversion ratio increased by 1.3% when CP was reduced by 1% point. The same CP reduction decreased daily nitrogen (N) excretion by 10.4% while N retention was not affected by CP. In conclusion, respecting the ideal protein concept with the use of feed-grade AA allows for a decrease in dietary CP and N excretion with limited impact on growth performance.